Analisis Struktur Rumah Susun 3 Lantai di Desa Margamekar Kecamatan Pangalengan Kabupaten Bandung - Roesdiana, Tira (Civil Engineering of Universitas Islam Nahdlatul Ulama Jepara, 2022)
Population growth in recent years in Bandung Regency has led to economic growth and development, but broadly developing the Bandung Regency area is not possible because most of the land is devoted to agricultural and plantation products. Therefore, upward development is more needed than extensive construction such as the construction of low and high-rise buildings. To do this, planners need to design a multi-storey building structure. One way to do this is to build Flats. Flats are very suitable in this case because in its construction it saves land use. In this analysis using the ETABS application and using the SNI Gedungb regulations according to their use.